Path analysis of yield and quality determinations in Thompson Seedless grape (Vitis vinefera) and its clones - SHIKHAMANY, S D; BORADE, SWAPNIL V; JEUGHALE, SANJAY K; PATIL, SURYAKANT Y (The Indian Journal of Agricultural Sciences, 2018)
Attempts were made to delineate the correlation coefficients of the vine, cluster and berry parameters with yield and quality in to direct and indirect effects in Thompson Seedless grape (Vitis vinifera L.) and its clones, namely Tas-A-Ganesh and 2A clone by Path Coefficient Analysis. Yield was influenced most, directly by cluster weight in Thompson Seedless, while by canes/vine in Tas-A-Ganesh; indirectly by berry diameter via cluster weight in the former variety, while by canes/vine via berries/cluster in the latter. When the negative effects on yield were considered, the direct effect of berries/cluster was highest in Thompson Seedless, while it was of berries/cluster in Tas-A-Ganesh. Among the indirect negative effects, cluster weight through berry diameter was highest in Thompson seedless, but berries/cluster through canes/vine in Tas-A-Ganesh. All the parameters included in the study could determine the yield in 2A clone by only 1.0 per cent, as the residual effect was 0.99. The corresponding residual values were 0.506 for Thompson Seedless and 0.516 for Tas-A- Ganesh.